Comparison of the Effect of Using Virtual Laboratory Based on PhET Simulation and Real Laboratory in Improving Mastery of Electronic Concepts of Physics Education Students - Fitriani, Annisa (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2024)
This study aimed to compare the mastery of electronic concepts among physics education students using a constructivist virtual laboratory (PhET Simulation) and a real constructivist laboratory. The importance of this research lies in the potential of virtual laboratories as an alternative to physical ones, especially when resources are limited. The research employed a quasi-experimental design with a matching-only posttest-only control group. The sample consisted of 68 physics education students from UIN Alauddin Makassar, divided into two groups: one using PhET Simulation (34 students) and the other using real laboratories (34 students). Data were collected through multiple-choice tests designed to measure concept mastery, analyzed using descriptive statistics and inferential tests such as t-tests. The results showed no significant difference in concept mastery between students using PhET Simulation and those using real laboratories (t =-0.167, p= 0.868). Both methods were equally effective in enhancing students’ understanding of electronics. The novelty of this study lies in directly comparing the two laboratory approaches within a constructivist framework. This finding suggests that virtual laboratories can serve as a viable alternative to real laboratories in supporting concept mastery, offering flexibility and resource efficiency. The implications of the study are particularly relevant for educational institutions with limited access to physical laboratories, as PhET Simulation provides a cost-effective solution without compromising learning outcomes.